The structure of the yeast mitochondrial ribosome* - Desai, Nirupa (Science, 2017)
Mitochondria have specialized ribosomes (mitoribosomes) dedicated to the expression of the genetic information encoded by their genomes. Here, using electron cryomicroscopy, we have determined the structure of the 75-component yeast mitoribosome to an overall resolution of 3.3 Å. The mitoribosomal small subunit has been built de novo and includes 15S rRNA and 34 proteins, including 14 without homologs in the evolutionarily related bacterial ribosome. Yeast-specific rRNA and protein elements, including the acquisition of a putatively active enzyme, give the mitoribosome a distinct architecture compared to the mammalian mitoribosome. At an expanded mRNA channel exit, there is a binding platform for translational activators that regulate translation in yeast but not mammalian mitochondria. The structure provides insights into the evolution and species-specific specialization of mitochondrial translation.